(Im)maturity in Tumor Ecosystem - Mortezaee, Keywan; Majidpoor, Jamal (Frontiers in Oncology, 2022)
Tumors have special features that make them distinct from their normal counterparts. Immature cells in a tumor mass and their critical contributions to the tumorigenesis will open new windows toward cancer therapy. Incomplete cellular development brings versatile and unique functionality in the cellular tumor ecosystem, such as what is seen for highly potential embryonic cells. There is evidence that maturation of certain types of cells in this ecosystem can recover the sensitivity of the tumor. Therefore, understanding more about the mechanisms that contributed to this immaturity will render new therapeutic approaches in cancer therapy. Targeting such mechanisms can be exploited as a supplementary to the current immunotherapeutic treatment schedules, such as immune checkpoint inhibitor (ICI) therapy. The key focus of this review is to discuss the impact of (im)maturity in cellular tumor ecosystems on cancer progression, focusing mainly on immaturity in the immune cell compartment of the tumor, as well as on the stemness of tumor cells.